2018
DOI: 10.1371/journal.pone.0194819
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high bloodpressure, hyperglycemia, dyslipidemia, metabolic syndrome and their determinants in Ethiopia: Evidences from the National NCDs STEPS Survey, 2015

Abstract: The prevalence of diabetes, dyslipidemias, and high blood pressure is increasing worldwide especially in low and middle income countries. World Health Organization has emphasized the importance of the assessment of the magnitude of the specific disease in each country. We determined the prevalence and determinant factors of high blood pressure, hyperglycemia, dyslipidemias and metabolic syndrome in Ethiopia. A community based survey was conducted from -April to June 2015 using WHO NCD STEPS instrument version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
123
23
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(173 citation statements)
references
References 37 publications
(40 reference statements)
24
123
23
3
Order By: Relevance
“…The finding of the present study is consistent with the findings on the prevalence of hypertension in Hawassa (19.7%) (8) Mekelle (19.1%) (5) and the national prevalence (15.8%) (7). However, it is lower than the findings of the studies in Addis Ababa (32.3%) (15), Jigjiga (28.3%) (10), Durame (22.4%) (12), Bahir dar (23.5%) (22) and Gonder (28.3%) (13) and higher than the findings of the studies in Jimma (13.2%) (11) and Sidama zone (9.9%) (9).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of the present study is consistent with the findings on the prevalence of hypertension in Hawassa (19.7%) (8) Mekelle (19.1%) (5) and the national prevalence (15.8%) (7). However, it is lower than the findings of the studies in Addis Ababa (32.3%) (15), Jigjiga (28.3%) (10), Durame (22.4%) (12), Bahir dar (23.5%) (22) and Gonder (28.3%) (13) and higher than the findings of the studies in Jimma (13.2%) (11) and Sidama zone (9.9%) (9).…”
Section: Discussionsupporting
confidence: 93%
“…In Ethiopia, according to the finding from WHO STEPS survey of 2015, the prevalence of hypertension was found to be 15.8% (7). There are also few studies reported the prevalence of hypertension varying from 8% to 35% (5, 8-16).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic meta-analysis from Ethiopia showed about 19.6% prevalence of hypertension with a higher proportion in urban than rural [8]. Similarly, a 15.8% prevalence of raised blood pressure was reported from the national NCDs STEPS survey in 2015 [9].…”
Section: Introductionmentioning
confidence: 87%
“…Studies have shown that sub-Saharan African countries, including Ethiopia, are experiencing a surge in the prevalence of DM resulting from rapid demographic, sociocultural, and economic transitions [3,4]. Based on a national survey, researchers have recently reported a DM prevalence of 3.2% (3.5% males and 3.0% females) in Ethiopia [5]. Type 2 diabetes-a global epidemic of our century-accounts for more than 90-95% of DM disease [6].…”
Section: Introductionmentioning
confidence: 99%